Analisis Pemeliharaan Perawatan Mesin Pilling Menggunakan Metode RCM, FMEA dan LTA - Anisa Rahmawati; Yustina Suhandini Tjahjaningsih; Mustakim Mustakim; Tri Prihatiningsih; Aries Budi Wijayanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to apply Reliability Centered Maintenance (RCM), Failure Mode and Effect Analysis (FMEA), and Logic Tree Analysis (LTA) methods to improve pilling machine performance at PT. Amak Firdaus Utomo. Through this systematic approach, the long and cross cutter components were identified as having the highest priority, with a value of 243, a failure frequency of 24 times, and a total downtime of 580 minutes. These components are categorized as having power outages, are critical, and represent the primary failure mode, thus requiring special attention in their maintenance strategy. Based on the analysis, a preventive maintenance strategy was established for the high-priority components, while other components were subject to condition-based maintenance. The application of this method has proven to produce a more optimal and efficient maintenance strategy, while supporting the overall resolution and performance of the pilling machine.